Intelligent Analysis of Computer-Aided Garment Design CAD Based on Virtual Reality Model for Surplus Fabric Removal and Reuse without Segmentation of Cutting Pieces - Tanqiu Wang (Advances in Multimedia)
For the purpose of improving the efficiency of garment design, the computer-aided garment design virtual reality (VR) model for surplus fabric removal and reuse without segmentation of cutting pieces is analyzed in this paper to provide the architecture of the computer-aided garment design CAD system. The form of dividing the garment into multiple types of nonsegmented pieces is adopted so that each nonsegmented piece stands for a complete design element unit. Based on this structure, the computer analysis of garment design based on CAD can be connected at a deeper level, which will not only improve the design efficiency of new garments but also reduce the design time at the client terminal and enhance the quality of the design. Through the experimental operation of prototypes, it is verified that the intelligent system proposed in this paper can implement the design of prototypes quickly and effectively.